Therapeutic properties, SOD and catecholase mimetic activities of novel ternary copper(II) complexes of the anti-inflammatory drug Fenoprofen with imidazole and caffeine - Agotegaray, Mariela Alejandra (2012)
The copper(II) ternary complexes of the non-steroidal anti-inflammatory drug Fenoprofen (Hfen) and the biologically relevant molecules imidazole (im) and caffeine (caf) as auxiliary ligands were investigated as novel anti-inflammatory agents. The new copper(II) complexes with formula [Cu(fen) 2(im) 2] (1) and Cu 2(fen) 4(caf) 2 (2) were synthesized from the dinuclear complex [Cu 2(fen) 4(dmf) 2] and characterized by IR, UV-Vis, EPR spectral and elemental analysis. The molecular structure of complex 1 was determined by X-ray crystallography. Both complexes 1 and 2 present enhanced and prolongued anti-inflammatory properties against the parent drug calcium Fenoprofenate, Ca(fen) 2·2H 2O, with a better performance for complex 1. Ternary complexes are potential models for several mono and poly-nuclear metal enzymes. The measured superoxide dismutase (SOD) mimetic activities of the complexes indicated a higher SOD mimic activity for complex 2 (IC 50 of 0.24 μM) than complex 1 (IC 50 of 0.70 μM), and also than the native enzyme evaluated by the same method (IC 50 of 0.480 μM). The catecholase activity of the complexes toward the aerobic oxidation of 3,5-di-tert-butylcatechol (dtbc) onto 3,5-di-tert-butylquinone (dtbq) showed that both complexes have moderate catalytic oxidase activity.